Scientists develop new digital tools for enhancing water management in a changing climate - Ojanji, Wandera (CGIAR System Organization, 2025)
Climate change is placing increasing pressure on water resources, particularly in regions where agricultural systems are highly vulnerable to climate variability and extremes. This blog presents recent work by CGIAR scientists to develop and deploy digital tools that enhance water management under changing climatic conditions. These tools integrate climate projections, hydrological modelling, and real-time data to support informed decision-making by policymakers, water managers, and agricultural stakeholders. By enabling improved forecasting, more efficient water allocation, and adaptive planning, the tools aim to strengthen resilience across food, land, and water systems. The blog highlights the potential of digital innovations to bridge science and practice, supporting climate adaptation efforts and more sustainable water governance in low- and middle-income countries.